2018
DOI: 10.1002/csr.1670
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion of corporate social responsibility through social network ties: From the perspective of strategic imitation

Abstract: Drawing on institutional and organizational learning theories, this study empirically investigates the imitation of corporate social responsibility (CSR) between firms tied by board interlocks, an important type of corporate social network tie. We propose a positive relationship between the CSR engagement of a focal firm and that of its tied-to partners and examine how this relationship is moderated by the characteristics of both the focal and tied-to firms. Using a sample of Chinese-listed companies, empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 73 publications
0
54
0
1
Order By: Relevance
“…The authors highlight that this is because the knowledge that is needed for substantive CSR engagement is sticky. However, the study highlights that such substantive engagement may be facilitated by the selected governance structure, culture, or capability development [167].…”
Section: Contextmentioning
confidence: 93%
See 3 more Smart Citations
“…The authors highlight that this is because the knowledge that is needed for substantive CSR engagement is sticky. However, the study highlights that such substantive engagement may be facilitated by the selected governance structure, culture, or capability development [167].…”
Section: Contextmentioning
confidence: 93%
“…Environmental conditions are often explained using theories such as stakeholder theory [138,166] or institutional theory [133,164,167]. These scholars focus on 'institutional pressures' or 'stakeholder pressures' that create a form of legitimacy crisis on firms, which then motivate them to enter collaborative relationships and engage in inter-organizational learning.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Board ties to other firms provide a unique opportunity for directors to exchange information, to observe the business practices of their peers, create new business opportunities, and to obtain general business information [1,8,9]. Thus, research has shown that corporate practices that are shared among firms via board interlocks tend to have an impact on the dissemination of innovation [10][11][12][13], diversification strategies [4], the adoption of golden parachutes and social corporate responsibility practices [14], stock options and poison pills [15,16], as well as the creation of joint ventures [17] and the adoption of multidivisional organization forms [18].…”
Section: Introductionmentioning
confidence: 99%